Ammonium-Generating Microbial Consortia in Paddy Soil Revealed by DNA-Stable Isotope Probing and Metatranscriptomics - Chao-Nan Wang; Yoko Masuda; Keishi Senoo (Microorganisms)
Rice paddy fields are sustainable agricultural systems as soil microorganisms help maintain nitrogen fertility through generating ammonium. In these soils, dissimilatory nitrate reduction to ammonium (DNRA), nitrogen fixation, and denitrification are closely linked. DNRA and denitrification share the same initial steps and nitrogen gas, the end product of denitrification, can serve as a substrate for nitrogen fixation. However, the microorganisms responsible for these three reductive nitrogen transformations, particularly those focused on ammonium generation, have not been comprehensively characterized. In this study, we used stable isotope probing with 15NO3−, 15N2O, and 15N2, combined with 16S rRNA high-throughput sequencing and metatranscriptomics, to identify ammonium-generating microbial consortia in paddy soils. Our results revealed that several bacterial families actively contribute to ammonium generation under different nitrogen substrate conditions. Specifically, Geobacteraceae (N2O and +N2), Bacillaceae (+NO3− and +N2), Rhodocyclaceae (+N2O and +N2), Anaeromyxobacteraceae (+NO3− and +N2O), and Clostridiaceae (+NO3− and +N2) were involved. Many of these bacteria participate in key ecological processes typical of paddy environments, including iron or sulfate reduction and rice straw decomposition. This study revealed the ammonium-generating microbial consortia in paddy soil that contain several key bacterial drivers of multiple reductive nitrogen transformations and suggested their diverse functions in paddy soil metabolism.